PENGENALAN KONSEP DAN KONTEKS ARSITEKTUR PARHYANGAN BERDASARKAN ASTA KOSALA KOSALI BAGI PEMANGKU DAN SERATI PADA DIKLAT KEPEMANGKUAN DAN TUKANG BANTEN DI GRIYA GEDE MANIK UMAJATI, PEMOGAN, DENPASAR SELATAN - I Putu Gede Suyoga (Jurnal Lentera Widya, 2023)
One of the basic knowledge regarding the architecture of the parhyangan or the area and sacred places (temple) of Hindu worship should be understood by uncles or pinandita, Serati or banten artisans, and traditional prajuru as administrators of traditional villages in an effort to protect Hindus. Training (education and training) is an effective means of achieving this goal. Provision of learning materials with interactive lecture methods and practice. Training activities with concept material and architectural context parhyangan through kepamangkuan, serati, and traditional prajuru training activities organized by the Griya Gede Manik Umajati Foundation. The results of the study show that by placing worship architectural works as a sign system, through the theory of semiotics as a science of signs, it can be understood the content of the signifier and the signified or their form, function, and meaning. The understanding of the 40 participants at the beginning of the training showed that on average 74 percent understood the Parhyangan architectural work only in terms of its architectural form or appearance and function (signs/markers), while 26 percent did not understand in terms of meaning (signature). Both regarding spatial, building, and worship. After the training took place, the results of the evaluation showed an increase in participants' understanding of the complexity of the Parhyangan architectural work, which concerns the conception and philosophy that underlies it. context in the form of status of the temple, characteristics, radius of sanctity, variants of spatial and building layouts, functions, choice of good days for construction, rituals, and worship spells. The evaluation results showed an average increase of 99 percent of the participants' understanding of the training material, while 1 percent still needed further elaboration, especially regarding the new model of shrine phenomena, ceremonies, and worship spells. The pre-posttest results showed an average increase in understanding for all participants by 25 percent. and cult spells.